A high barrier PET / PE composite sheet and preparation method thereof

By hot-pressing the modified PET material with the PE material and using silicone resin bonding components containing particles, the problem of insufficient barrier properties of a single-layer PET sheet is solved, and a PET/PE composite sheet with high barrier and high mechanical properties is achieved.

CN119175927BActive Publication Date: 2025-03-04TIANJIN RUISHENG ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411698861.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-04
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

In the prior art, the barrier properties of a single-layer PET sheet are insufficient and cannot meet the needs of improving the barrier properties of food packaging materials.

Method used

By hot-pressing the modified PET material with the PE material, a high barrier PET/PE composite sheet is formed. The modified PET material enhances its binding ability to the bonding layer through surface treatment and the use of modifiers. The bonding layer is combined with a silicone resin bonding component containing particles and a monomer solution to improve crosslinking and mechanical properties.

Benefits of technology

The preparation of high-barrier PET/PE composite sheet is achieved, which significantly improves its mechanical strength and barrier properties and reduces oxygen permeability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a high barrier PET / PE composite sheet and a preparation method thereof, wherein the composite sheet is formed by hot pressing a modified PET material and a PE material, wherein the PE material is located above the modified PET material, and an adhesive layer is provided between the modified PET material and the PE material; the modified PET material is formed by modifying a surface-treated PET material by a modifier. The PET / PE composite sheet of the present invention first modifies the PET material, and compared with the original PET material, it can better combine with the adhesive solution, thereby improving the overall mechanical strength of the composite sheet, and at the same time, through the combination of a monomer solution containing microparticles and a silicone resin adhesive component, the overall cross-linking of the adhesive layer is improved, and the oxygen permeability of the composite sheet is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemistry, and in particular relates to a high-barrier PET / PE composite sheet and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate (PET) resin is a milky white or light yellow, highly crystalline polymer with excellent physical and mechanical properties over a wide temperature range. The long-term use temperature can reach 120°C. It has excellent electrical insulation and good creep resistance, fatigue resistance, friction resistance and dimensional stability.

[0003] Polyethylene (PE) resin, also known as odorless, non-toxic, has excellent low temperature resistance, chemical stability, acid and alkali resistance, and is the largest user of film products.

[0004] The purpose of food packaging is to protect food from the external environment and prevent food from being contaminated by physical, chemical and microbial factors in the environment, which will shorten the shelf life of food and affect the value of the food itself. Considering comprehensive performance, cost and durability, plastic has become the preferred material for food packaging applications. In today's market, the most common plastic materials used for food packaging are polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC) and polyethylene terephthalate (PET).

[0005] With the continuous improvement of chemical technology and people's living standards, the barrier properties of single-layer PET sheets can no longer meet the needs, so there is an urgent need to develop a high-barrier PET / PE material. Summary of the invention

[0006] In view of this, the present invention aims to overcome the defects in the prior art and proposes a high barrier PET / PE composite sheet and a preparation method thereof.

[0007] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0008] A high barrier PET / PE composite sheet, wherein the composite sheet is formed by hot pressing a modified PET material and a PE material, wherein the PE material is located above the modified PET material, and an adhesive layer is provided between the modified PET material and the PE material; and the modified PET material is formed by modifying a surface-treated PET material with a modifier.

[0009] Furthermore, the adhesive layer is obtained by immersing the modified PET material in an adhesive solution containing microparticles and then drying the modified PET material.

[0010] Furthermore, the bonding solution containing microparticles comprises a silicone bonding component and a monomer solution containing microparticles in a mass ratio of 1:2-50.

[0011] Preferably, the bonding solution containing microparticles comprises a silicone bonding component and a monomer solution containing microparticles in a mass ratio of 1:2-10.

[0012] The preparation method of the silicone resin bonding component comprises the following steps:

[0013] (1) Add 10 kg of toluene and 15 kg of pure water to the reactor, stir, then add 20 kg of dimethyldichlorosilane, 25 kg of phenyltrichlorosilane and 30 kg of toluene to the header tank and mix evenly;

[0014] (2) Slowly and uniformly add the halogenated silane toluene mixture in the high-level tank to the reactor. The addition time is 5 hours. The reactor temperature is 25-40°C. After the addition is completed, continue stirring for 2 hours.

[0015] (3) Let the solution stand and separate, remove the lower aqueous phase, retain the upper organic phase, and wash the organic phase with water until the pH value is 6;

[0016] (4) Add 3.5 kg of sodium tetraborate and stir for 2 h until completely dissolved. Heat the reactor to 90-120 °C and remove the organic solvent and residual water by vacuum distillation at -0.03 MPa;

[0017] (5) Add 0.3 kg of catalyst zinc octoate, raise the temperature to 140 ° C, and carry out polymerization for 2.5 hours. After the polymerization is completed, cool down to 60-80 ° C, add 2 kg of isopropanol, 1.2 kg of coupling agent KH792, and toluene, and adjust the solid content to 18%.

[0018] Furthermore, the preparation method of the monomer solution containing microparticles comprises the following steps: dissolving N-hydroxymethyl acrylamide and methoxy polyethylene glycol monomethacrylate in a solvent to obtain a monomer solution, dissolving an azo initiator in a solvent to obtain an initiator solution, and respectively dropping the monomer solution and the initiator solution into the solvent under a nitrogen atmosphere, heating and stirring after the dropping is completed, and obtaining the bonding solution containing microparticles after the reaction is completed.

[0019] Part of the functional groups of the monomer solution containing microparticles undergo condensation reaction to obtain microparticles, thereby improving the overall viscosity of the solution. Other unreacted functional groups react with the groups of the silicone resin bonding component to make the overall bonding layer more tightly cross-linked, thereby improving the overall mechanical properties of the composite sheet while blocking oxygen.

[0020] Furthermore, the mass ratio of N-hydroxymethyl acrylamide, methoxy polyethylene glycol monomethacrylate and azo initiator is 50-80:20-50:15; the temperature of the dropwise addition step is 80-120° C.; the temperature of the heating and stirring step is 80-120° C.; and the solvent is methoxypropanol.

[0021] Furthermore, the preparation method of the modified PET material comprises the following steps:

[0022] Step 1 is to immerse the PET material in an acid solution to obtain a PET material with a rough surface;

[0023] Step 2 is to immerse the rough-surfaced PET material in a modifier under heating conditions, and then dry it to obtain the modified PET material.

[0024] Furthermore, the acid solution in step 1 is dilute sulfuric acid; the soaking step in step 1 is performed for 1-10 hours; the heating step in step 2 is performed at a temperature of 30-80° C.; and the soaking step in step 2 is performed for 1-10 hours.

[0025] Furthermore, the preparation method of the modifier in step 2 comprises the following steps: uniformly mixing a branched polyethyleneimine ethanol solution and a pentaerythritol pentaacrylate ethanol solution, stirring to obtain a nanocomposite solution, adding chitosan and acetic acid to deionized water, stirring to obtain a chitosan solution, and uniformly mixing the nanocomposite solution and the chitosan solution to obtain the modifier.

[0026] The nanocomposite solution obtained by the reaction of branched polyethyleneimine and pentaerythritol pentaacrylate reacts with the chitosan solution to generate a cross-linked structure, which has a stronger bonding force with the substrate; after the PET material is treated with acid, the specific surface area of ​​the PET substrate is increased, and more cross-linked structures can be combined, thereby improving the overall strength of the modified PET material and making it more firmly bonded to the PE material through the bonding solution.

[0027] Furthermore, the concentration of the branched polyethyleneimine ethanol solution is 1-30 mg / mL; the concentration of the pentaerythritol pentaacrylate ethanol solution is 10-50 mg / mL; the volume ratio of the branched polyethyleneimine ethanol solution to the pentaerythritol pentaacrylate ethanol solution is 1:1-5; the solid-liquid ratio of the chitosan to acetic acid and deionized water is 0.1-1 g:1-5 g:100 mL; and the volume ratio of the nanocomposite solution to the chitosan solution is 10-50:10.

[0028] The present invention also provides a method for preparing a high-barrier PET / PE composite sheet, comprising the following steps: coating the surface of the modified PET material with the bonding solution containing microparticles, and obtaining the high-barrier PET / PE composite sheet by hot pressing with the PE material after drying.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] The high-barrier PET / PE composite sheet of the present invention first modifies the PET material, which can be better combined with the bonding solution compared with the original PET material, thereby improving the overall mechanical strength of the composite sheet. At the same time, through the combination of the monomer solution containing particles and the silicone resin bonding component, the overall cross-linking of the bonding layer is improved, and the oxygen permeability of the composite sheet is reduced. DETAILED DESCRIPTION

[0031] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0032] The silicone resin bonding components in the embodiments of the present invention and the comparative examples are prepared by a method comprising the following steps:

[0033] (1) Add 10 g of toluene and 15 g of pure water to the reactor, stir, then add 20 g of dimethyldichlorosilane, 25 g of phenyltrichlorosilane and 30 g of toluene to the header tank and mix well;

[0034] (2) Slowly and uniformly add the halogenated silane toluene mixture in the high-level tank to the reactor. The addition time is 5 hours. The reactor temperature is 25-40°C. After the addition is completed, continue stirring for 2 hours.

[0035] (3) Let the solution stand and separate, remove the lower aqueous phase, retain the upper organic phase, and wash the organic phase with water until the pH value is 6;

[0036] (4) Add 3.5 g of sodium tetraborate and stir for 2 h until completely dissolved. Heat the reactor to 90-120 °C and remove the organic solvent and residual water by vacuum distillation at -0.03 MPa.

[0037] (5) Add 0.3 g of catalyst zinc octoate, raise the temperature to 140 °C, and conduct polymerization reaction for 2.5 h. After the polymerization is completed, cool down to 60-80 °C, add 2 g of isopropanol, 1.2 g of coupling agent KH792, and toluene, and adjust the solid content to 18%.

[0038] The monomer solutions containing microparticles in the examples of the present invention and the comparative examples are prepared by a method comprising the following steps:

[0039] (1) dissolving 60 g of N-hydroxymethyl acrylamide and 40 g of methoxy polyethylene glycol monomethacrylate in 200 g of methoxypropanol to obtain a monomer solution;

[0040] (2) dissolving 1 g of an azo initiator in 50 g of a solvent to obtain an initiator solution;

[0041] (3) The obtained monomer solution and initiator solution were respectively added dropwise to 150 g of solvent under nitrogen atmosphere at 100° C. After the addition was completed, the mixture was stirred at 100° C. After the reaction was completed, the bonding solution containing microparticles was obtained.

[0042] The present invention will be described in detail below with reference to the embodiments.

[0043] Example 1

[0044] A method for preparing a high barrier PET / PE composite sheet comprises the following steps:

[0045] (1) 10 mL of branched polyethyleneimine ethanol solution (20 mg / mL) and 40 mL of pentaerythritol pentaacrylate ethanol solution (30 mg / mL) were mixed evenly, and ethanol was added thereto after stirring to obtain a nanocomposite solution with a concentration of 5 mg / mL. 0.3 g of chitosan and 1 g of acetic acid were added to 100 g of deionized water, and the mixture was stirred for 1 hour to obtain a chitosan solution. The nanocomposite solution and the chitosan solution were mixed evenly to obtain the modifier.

[0046] (2) immersing the PET material in dilute sulfuric acid for 5 hours to obtain a PET material with a rough surface, immersing the PET material with a rough surface in the modifier at 60° C., taking it out after 5 hours, and then drying it to obtain the modified PET material;

[0047] (3) adding 20 g of a silicone resin bonding component to 80 g of a monomer solution containing microparticles, and mixing them evenly to obtain the bonding solution containing microparticles;

[0048] (4) The modified PET material is coated with the bonding solution containing microparticles, and after drying, the modified PET material is hot-pressed with the PE material to obtain the PET / PE composite sheet.

[0049] Example 2

[0050] A method for preparing a high barrier PET / PE composite sheet comprises the following steps:

[0051] (1) 10 mL of branched polyethyleneimine ethanol solution (20 mg / mL) and 20 mL of pentaerythritol pentaacrylate ethanol solution (40 mg / mL) were mixed evenly, and ethanol was added thereto after stirring to obtain a nanocomposite solution with a concentration of 5 mg / mL, 0.3 g of chitosan and 1 g of acetic acid were added to 100 g of deionized water, and the mixture was stirred for 1 hour to obtain a chitosan solution, and the nanocomposite solution and the chitosan solution were mixed evenly to obtain the modifier;

[0052] (2) immersing the PET material in dilute sulfuric acid for 5 hours to obtain a PET material with a rough surface, immersing the PET material with a rough surface in the modifier at 60° C., taking it out after 5 hours, and then drying it to obtain the modified PET material;

[0053] (3) adding 10 g of a silicone resin bonding component to 80 g of a monomer solution containing microparticles, and mixing them evenly to obtain the bonding solution containing microparticles;

[0054] (4) The modified PET material is coated with the bonding solution containing microparticles, and after drying, the modified PET material is hot-pressed with the PE material to obtain the PET / PE composite sheet.

[0055] Comparative Example 1

[0056] A method for preparing a high barrier PET / PE composite sheet comprises the following steps:

[0057] (1) 10 mL of branched polyethyleneimine ethanol solution (20 mg / mL) and 40 mL of pentaerythritol pentaacrylate ethanol solution (30 mg / mL) were mixed evenly, and ethanol was added thereto after stirring to obtain a nanocomposite solution with a concentration of 5 mg / mL. 0.3 g of chitosan and 1 g of acetic acid were added to 100 g of deionized water, and the mixture was stirred for 1 hour to obtain a chitosan solution. The nanocomposite solution and the chitosan solution were mixed evenly to obtain the modifier.

[0058] (2) immersing the PET material in dilute sulfuric acid for 5 hours to obtain a PET material with a rough surface, immersing the PET material with a rough surface in the modifier at 60° C., taking it out after 5 hours, and then drying it to obtain the modified PET material;

[0059] (3) The monomer solution containing microparticles is coated on the surface of the modified PET material, and after drying, the solution is hot-pressed with the PE material to obtain the PET / PE composite sheet.

[0060] Comparative Example 2

[0061] A method for preparing a high barrier PET / PE composite sheet comprises the following steps:

[0062] (1) 10 mL of branched polyethyleneimine ethanol solution (20 mg / mL) and 40 mL of pentaerythritol pentaacrylate ethanol solution (30 mg / mL) were mixed evenly, and ethanol was added thereto after stirring to obtain a nanocomposite solution with a concentration of 5 mg / mL. 0.3 g of chitosan and 1 g of acetic acid were added to 100 g of deionized water, and the mixture was stirred for 1 hour to obtain a chitosan solution. The nanocomposite solution and the chitosan solution were mixed evenly to obtain the modifier.

[0063] (2) immersing the PET material in dilute sulfuric acid for 5 hours to obtain a PET material with a rough surface, immersing the PET material with a rough surface in the modifier at 60° C., taking it out after 5 hours, and then drying it to obtain the modified PET material;

[0064] (3) The silicone resin bonding component is coated on the surface of the modified PET material, and after drying, the modified PET material is hot-pressed with the PE material to obtain the PET / PE composite sheet.

[0065] Comparative Example 3

[0066] A method for preparing a high barrier PET / PE composite sheet comprises the following steps:

[0067] (1) 10 mL of branched polyethyleneimine ethanol solution (20 mg / mL) and 40 mL of pentaerythritol pentaacrylate ethanol solution (30 mg / mL) were mixed evenly, and ethanol was added thereto after stirring to obtain a nanocomposite solution with a concentration of 5 mg / mL. 0.3 g of chitosan and 1 g of acetic acid were added to 100 g of deionized water, and the mixture was stirred for 1 hour to obtain a chitosan solution. The nanocomposite solution and the chitosan solution were mixed evenly to obtain the modifier.

[0068] (2) immersing the PET material in dilute sulfuric acid for 5 hours to obtain a PET material with a rough surface, immersing the PET material with a rough surface in the modifier at 60° C., taking it out after 5 hours, and then drying it to obtain the modified PET material;

[0069] (3) adding 100 g of the monomer solution containing microparticles to 200 g of the silicone resin bonding component and mixing them evenly to obtain the bonding solution containing microparticles;

[0070] (4) The modified PET material is coated with the bonding solution containing microparticles, and after drying, the modified PET material is hot-pressed with the PE material to obtain the PET / PE composite sheet.

[0071] Comparative Example 4

[0072] A method for preparing a high barrier PET / PE composite sheet comprises the following steps:

[0073] (1) 10 mL of branched polyethyleneimine ethanol solution (20 mg / mL) and 40 mL of pentaerythritol pentaacrylate ethanol solution (30 mg / mL) were mixed evenly, and ethanol was added thereto after stirring to obtain a nanocomposite solution with a concentration of 5 mg / mL. 0.3 g of chitosan and 1 g of acetic acid were added to 100 g of deionized water, and the mixture was stirred for 1 hour to obtain a chitosan solution. The nanocomposite solution and the chitosan solution were mixed evenly to obtain the modifier.

[0074] (2) immersing the PET material in dilute sulfuric acid for 5 hours to obtain a PET material with a rough surface, immersing the PET material with a rough surface in the modifier at 60° C., taking it out after 5 hours, and then drying it to obtain the modified PET material;

[0075] (3) The PE material is placed on top of the modified PET material, and the PET / PE composite sheet is obtained by hot pressing.

[0076] Comparative Example 5

[0077] A method for preparing a high barrier PET / PE composite sheet comprises the following steps:

[0078] (1) Immersing the PET material in dilute sulfuric acid for 5 hours to obtain a modified PET material;

[0079] (2) adding 20 g of a silicone resin bonding component to 80 g of a monomer solution containing microparticles, and mixing them evenly to obtain the bonding solution containing microparticles;

[0080] (3) The modified PET material is coated with the bonding solution containing microparticles, and after drying, the modified PET material is hot-pressed with the PE material to obtain the PET / PE composite sheet.

[0081] The PET / PE composite sheets obtained in Example 1-2 and the PET / PE composite sheets obtained in Comparative Examples 1-5 were tested for water vapor transmission rate (GB / T 26253-2010, 38°C 90%RH), oxygen transmission rate (GB / T 19789-2005, 23°C 0%RH) and mechanical properties. The results are shown in Table 1.

[0082] Table 1 Test results

[0083]

[0084] As shown in Table 1, the water vapor permeability, oxygen permeability and peel strength of the composite sheets obtained in Examples 1-2 are greatly improved compared with those in the comparative examples; the combination of the silicone resin bonding component and the monomer solution containing microparticles makes the cross-linked structure inside the bonding layer more compact, promotes the reduction of water vapor permeability and oxygen permeability, and at the same time makes the PET material and the PE material more firmly bonded, thereby improving the peel strength of the composite sheet.

[0085] In Comparative Example 1, the monomer solution containing microparticles was used alone as the bonding solution, which reduced the performance of the composite sheet. In Comparative Example 2, the silicone resin bonding component was used alone as the bonding solution, which greatly reduced the performance of the composite sheet, indicating that the combination of the silicone resin bonding component and the monomer solution containing microparticles is indispensable, and the monomer solution containing microparticles has a more significant effect on the overall performance of the composite sheet; in Comparative Example 3, a large amount of silicone resin bonding component was added to the bonding layer, and the effect was significantly different compared with Examples 1-2; in Comparative Example 4, no bonding component was added, resulting in a significant reduction in its peel strength; in Comparative Example 5, the PET layer was not modified with a modifier, which also had a certain impact on the performance of the composite layer.

[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high barrier PET / PE composite sheet, characterized in that: The composite sheet is formed by hot pressing a modified PET material and a PE material, the PE material is located above the modified PET material, and an adhesive layer is provided between the modified PET material and the PE material; the modified PET material is formed by modifying the surface-treated PET material with a modifier; The adhesive layer is obtained by soaking the modified PET material in an adhesive solution containing microparticles and then drying the modified PET material to obtain the adhesive layer; The bonding solution containing microparticles comprises a silicone bonding component and a monomer solution containing microparticles in a mass ratio of 1:2-50; The preparation method of the monomer solution containing microparticles comprises the following steps: dissolving N-hydroxymethyl acrylamide and methoxy polyethylene glycol monomethacrylate in a solvent to obtain a monomer solution, dissolving an azo initiator in the solvent to obtain an initiator solution, respectively dropping the monomer solution and the initiator solution into the solvent under a nitrogen atmosphere, heating and stirring after the dropping is completed, and obtaining the bonding solution containing microparticles after the reaction is completed; The preparation method of the modified PET material comprises the following steps: Step 1 is to immerse the PET material in an acid solution to obtain a PET material with a rough surface; Step 2 is to immerse the rough-surfaced PET material in a modifier under heating conditions, and then dry it to obtain the modified PET material; The preparation method of the modifier in step 2 comprises the following steps: uniformly mixing a branched polyethyleneimine ethanol solution and a pentaerythritol pentaacrylate ethanol solution, stirring to obtain a nanocomposite solution, adding chitosan and acetic acid to deionized water, stirring to obtain a chitosan solution, and uniformly mixing the nanocomposite solution and the chitosan solution to obtain the modifier.

2. The high barrier PET / PE composite sheet according to claim 1, characterized in that: The mass ratio of N-hydroxymethyl acrylamide, methoxy polyethylene glycol monomethacrylate and azo initiator is 50-80:20-50:15; the temperature of the dropwise addition step is 80-120° C.; the temperature of the heating and stirring step is 80-120° C.; and the solvent is methoxypropanol.

3. The high barrier PET / PE composite sheet according to claim 1, characterized in that: The acid solution in step 1 is dilute sulfuric acid; the soaking step in step 1 lasts for 1-10 hours; the heating step in step 2 has a temperature of 30-80° C.; and the soaking step in step 2 lasts for 1-10 hours.

4. The high barrier PET / PE composite sheet according to claim 1, characterized in that: The concentration of the branched polyethyleneimine ethanol solution is 1-30 mg / mL; the concentration of the pentaerythritol pentaacrylate ethanol solution is 10-50 mg / mL; the volume ratio of the branched polyethyleneimine ethanol solution to the pentaerythritol pentaacrylate ethanol solution is 1:1-5; the solid-liquid ratio of the chitosan to acetic acid and deionized water is 0.1-1 g:1-5 g:100 mL; and the volume ratio of the nanocomposite solution to the chitosan solution is 10-50:

10.

5. The method for preparing the high barrier PET / PE composite sheet according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: coating the bonding solution containing microparticles on the surface of the modified PET material, and obtaining the high-barrier PET / PE composite sheet by hot pressing with the PE material after drying.

Citation Information

Patent Citations

  • High-barrier packaging material

    US20070110932A1